The Effectiveness of Criminalizing Hate Speech Through Electronic Media In Dealing With Social Changes of Communicating In Cyberspace - Dewa Gede Giri Santosa (Fakultas Hukum Universitas Lampung, 2021)
The existence of the internet has a positive impact and has a negative impact, one of which is the rampant hate speech that is spread through social media. The government then issued Law No. 11 of 2008 concerning Electronic Information and Transactions as amended by Law No. 19 of 2016, which regulates the criminalisation of hate speech conducted via electronic media. Nonetheless, even though there have been criminal threats against acts of hate speech through cyberspace, the number of cases of hate speech handled by the police has increased in years. The research aims to discover social changes' influence in the criminalisation of hate speech through electronic media. Moreover, the research investigates the criminalisation of hate speech's effectiveness through electronic media to tackle the rise of hate speech in cyberspace. This research uses the normative legal research method. The research explains that social changes related to sharing information via electronic media have an impact on applicable law in Indonesia with regulations regarding hate speech through electronic media. However, since the enactment of this regulation, hate speech acts through electronic media has increased. Therefore, the criminalisation policy must pay attention to the principle of subsidiarity. Criminal law must be the last resort in overcoming crimes using a penal instrument. Other efforts needed that should be prioritised apart from punishing the perpetrators of criminal acts.